New Antiepileptic Drugs Revolution or Marketing Spin?. Issue 2 (1st December 2001) - Leach, John Paul; Marson, Tony; Chadwick, David
Abstract : INTRODUCTION Epilepsy is common, with a lifetime prevalence of 2–5% of the general population (Goodridge & Shorvon 1983a; Goodridge & Shorvon 1983b, Shorvon 1990) and a point prevalence of between 4 and 8 per 1000 (Hauser et al. 1993). Epilepsy represents a significant fraction of the workload for most neurologists, and indeed, never has specialist input been more necessary as the choice of antiepileptic drugs (AEDs) continues to grow: eight new AEDs have been licensed for use in the UK since the late 1980s, with the promise of more to come (Bialer et al. 2001). Despite these recent additions to the ranks of available anticonvulsants, epilepsy remains both stigmatizing and debilitating for many of those with the disorder (Reynolds 1990). This article deals with a number of issues surrounding the newer drugs. We will look at the certainties surrounding the older drugs, the possibilities surrounding the newer ones, and